Dam safety evacuation planning for community downstream of Pergau Dam, Jeli, Kelantan (case study of Kg Batu Melintang) - Mamat, Ahmad Fadhli; Md. Amin, Mohamad Faiq; Kamal, Nor Syafiqah; Muda, Rahsidi Sabri; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati (Springer Nature, 2024)
Dam safety evacuation planning is crucial to ensure the sustainability of hydro dam operations in the surrounding environment. One of the critical aspects that are being focused on at the moment is the dam safety for the community downstream of the dam itself, which normally will be the first to receive the direct impact from a dam-related incident. In this paper, focusing on the potential disaster of dam failure and the evacuation planning for the community downstream of a dam will be focused on. As a case study, the community downstream of Pergau Dam, covering the most populated area known as Kampung Batu Melintang, will be looked into. Evacuation planning covers mostly the evacuation route, evacuation shelter, and most importantly the critical function of an early warning system to initiate early preparation for evacuation.